THE EFFECT OF EXPERIENTIAL QUALITY AND EXPERIENTIAL VALUE ON TOURIST SATISFACTION IN LAKE TOBA OF SAMOSIR REGENCY - Alfifto Alfifto; Endang Sulistya Rini; Yeni Absah (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Tourism is a new type of industry that can accelerate economic growth and employment provision, increase income and standard of living, and stimulate other productive sectors. Samosir regency is a tourism destination that has captivated both international and domestic tourists because of the stunning natural beauty of Lake Toba.This study aims to discover and analyze the effect of experiential quality and experiential value on tourist satisfaction in Lake Toba, Samosir regency. The population in this study were tourists of unspecified number visiting Lake Toba in Samosir regency. The number of samples were 140 respondents. The study involved accidental sampling technique, questionnaire in data collection, and multiple linear regression on data analysis. The results of this study indicated that simultaneously experiential quality and experiential value significantly influenced tourist satisfaction in Lake Toba in Samosir Regency. Partial test showed that experiential quality and experiential value had a positive and significant effect on tourist satisfaction in Lake Toba, Samosir regency. Keywords: Experiential Quality, Experiential Value, Tourist Satisfaction